The Issue of Nagorno-Karabakh in 1921–1923: Distortions in Azerbaijani Historiography - Khachatryan , Armine (History and Culture, 2026)
This article examines the issue of Nagorno-Karabakh—the contradictions that arose around this matter in the period from July 5, 1921, when the decision was made to include the territory within Azerbaijan, to July 7, 1923, when the decision was made to grant autonomy and establish the Nagorno-Karabakh Autonomous Region [NKAR], as well as the efforts aimed at overcoming these contradictions. The essence of the researched problem lies in the fact that, in the historical and political literature, the situation that emerged after the decision to include Nagorno-Karabakh within Azerbaijan has not been thoroughly studied. In many cases, this issue is approached in a one-sided and biased manner. Meanwhile, the entire course of events related to one of the most acute conflicts of the 20th century—the Nagorno-Karabakh issue—demonstrates that the real consequences of the decisions made and attitudes toward the conflict require further clarification, and one-sided interpretations are unacceptable. At the same time, the reaction of the direct stakeholders—the Armenian population of Nagorno-Karabakh—has not received due attention. There are numerous studies on this issue in both Armenian and Azerbaijani historiographies. However, it should be emphasized that there are significant gaps, particularly in the form of extremely opposing positions on the problem. Our goal is to uncover the actual course of events and, ultimately, examine the issue in terms of how well it reflected the free will of the national majority and to what extent it was acceptable and just.
Keywords: Nagorno Karabakh; solution; autonomy; region; discontent; Soviet Azerbaijan; historiography; issue